TikTok's Social Media Marketing Activities (SMMA) on Willingness to Pay a Premium Price for Make Over Products - Noorita A, Ratu; lamama, Aco (Pascasarjana STIE Amkop Makassar, 2024)
This research aims to analyze the influence of TikTok's Social Media Marketing Activities (SMMA) on consumers' willingness to pay a premium price for MakeOver products, mediated by Brand Image and Brand Loyalty. The study employs a quantitative method. The sampling technique used is non-probability sampling with a purposive sampling approach. The population involved in this study includes all Indonesian consumers who have purchased and used MakeOver products, with a total of 185 participants. Data collection was conducted through questionnaires using a Likert scale. The data analysis technique employed is SEM PLS, which includes both Outer Model and Inner Model analysis using SMARTPLS 3.0 software. The study results indicate that SMMA has a significant and positive impact on willingness to pay a premium price through Brand Image and Brand Loyalty.Keywords: SMMA; Willingness to Pay a Premium Price; Brand Image; Brand Loyalty